Accidents, Injuries, and Safety among Artisanal and Small-Scale Gold Miners in Zimbabwe - Singo, Josephine; Isunju, John Bosco; Moyo, Dingani; Bose-O'Reilly, Stephan; Steckling-Muschack, Nadine (MDPI, 2022)
Artisanal and small-scale gold mining (ASGM) employs 14-19 million people globally. There is limited research on accidents, injuries, and safety in Zimbabwe's ASGM. This study investigates the prevalence of accidents and injuries, as well as the associated risks and existing safety practices. A cross-sectional survey was conducted among artisanal and small-scale gold miners. Data from 401 participants were analyzed using descriptive statistics and regression analysis. The prevalence of accidents and injuries was 35.0% and 25.7%. Accidents associated with experiencing injuries included mine collapses and underground trappings. The major injury risk factors were digging, blasting, being male, being 18-35 years old, crushing, and the underground transportation of workers and materials. Injuries were reported highest among the miners working 16 to 24 h per day. Participants had heard about personal protective equipment (PPE). There was training and routine inspections mainly on PPE use. Mine owners and supervisors were reported as responsible for OSH, which was mainly PPE use. Practices including the use of wire winch ropes and escape routes were rare. There was ignorance on underground mine shaft support. The mining regulations that had the potential to introduce comprehensive safety controls were not adaptable. We recommend applicable health and safety regulations for Zimbabwe's ASGM.